(3cJGH GdQJHI aj GdMSHIs
(3ChdgG (B:s
(3aUd ai TQGFW GdMSHI hUaI GdeMJSH GdMSHI ef bhGYO GdCehQ GdOjfjI hbO cGf CFeI GdUOQ GdChd jHGTQhfgG HCfaSge s
(3BNQgG (B:s
(3hjCeQge HGdeeQ ai GdCeGcf GdeJSYI hjLJgOhf ai YdagG ZGjI GdELJgGO hdh TYQJ ai LejY eG jaYdg GdeMJSH ef CehQ GdMSHI dWGd GdcdGe ai Pdc hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs